PRODUCTION COSTS OF FIELD CROPS BY ECONOMIC SIZE OF FARMS IN ROMANIA - Anca DACHIN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The cost competitiveness is a key topic in agriculture. Knowledge about costs at microeconomic level is a useful instrument for the orientation of producers, as well as for decision makers at aggregate levels. The paper focuses on the empirical analysis of production costs for field crops in Romania, using the methodology and data of the EU Farm Accountancy Data Network. The analysis takes into consideration the economic size of farms and is mostly relevant in the case of specialized farms. The cost structure reveals differences when comparing small with large farms and it provides a benchmark to individual farms when they need to know their position within their size class.